2015
DOI: 10.1017/hpl.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a high-order harmonic generation seeded extreme ultraviolet free electron laser by time-synchronization control with electro-optic sampling

Abstract: A fully coherent free electron laser (FEL) seeded with a higher-order harmonic (HH) pulse from high-order harmonic generation (HHG) is successfully operated for a sufficiently prolonged time in pilot user experiments by using a timing drift feedback. For HHG-seeded FELs, the seeding laser pulses have to be synchronized with electron bunches. Despite seeded FELs being non-chaotic light sources in principle, external laser-seeded FELs are often unstable in practice because of a timing jitter and a drift between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…However, highenergy charged particles have a relativistic effect called length contraction and their pulse widths (i.e., size in the propagation direction) shrink [1] . In particular, highly relativistic electron beams with pulse widths of a few tens of femtoseconds are utilized in high-order harmonic generation seeded free-electron lasers [2] . On the other hand, threedimensional beam sizes have a big impact on properties of generated X-ray pulses.…”
Section: Introductionmentioning
confidence: 99%
“…However, highenergy charged particles have a relativistic effect called length contraction and their pulse widths (i.e., size in the propagation direction) shrink [1] . In particular, highly relativistic electron beams with pulse widths of a few tens of femtoseconds are utilized in high-order harmonic generation seeded free-electron lasers [2] . On the other hand, threedimensional beam sizes have a big impact on properties of generated X-ray pulses.…”
Section: Introductionmentioning
confidence: 99%
“…36) The measurement of the spatio-temporal, or transverse (radial) and longitudinal, profile of the electron beam is essential especially in a high-order harmonic generation seeded FEL. 37) This is because the electron bunch and the higherharmonic pulse need to be overlapped three-dimensionally while passing through the undulator. It was reported that the central location and the transverse spatial moment (the shape of the electron bunch) with the pulse width were successfully determined by EO sampling.…”
mentioning
confidence: 99%